Survey on the small mammals in Sg. Kangkawat research station Imbak canyon conservation areas - Lawrence Alan Bansa; Qhairil Shyamri Rosli; Ummu Safiyyah Daud; Amirrah Amat; Muhd Amsyari Morni; Julius William Dee; Emy Ritta Jinggong; Praveena Rajasegaran; Juliana Senawi; Jayaraj Vijaya Kumaran; Isham Azhar; Azniza Mahyudin; et al. (Journal of Tropical Biology and Conservation, 2020)
Sg. Kangkawat Research Station is a newly established research station in the Imbak Canyon Conservation Area, Sabah which encompasses both primary and secondary forest areas. Limited data is available on the small mammal diversity for this particular area. Therefore, a survey-based study on small mammal diversity was carried out between the 29th September – 8th October 2018 along the established trails within the vicinity areas of this research station. Small mammal trapping was done using traps (mist nets, harp traps, cage traps and pitfall traps) employed randomly along the Nepenthes trail, the Kawang trail, the South Rim trail and the Pelajau trail. This study documented a total of 32 small mammal species i.e. represented by 26 species (15 spp. of new records for ICCA ) of volant small mammals (Chiroptera) and 6 species of non-volant small mammals (Rodentia, Scadentia, Insectivora, Carnivora). The total number of specimens recorded was 108. A new distribution record on the Free-tailed Bat, Chaerephon cf. johorensis, was documented for Sabah and Borneo during this study.